Proceedings of the 15th International Symposium on Management (INSYMA 2018) 2018
DOI: 10.2991/insyma-18.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate governance on the capital structure of non-financial companies in the period of 2011-2015

Abstract: The purpose of the research was to analyze the effect of Corporate Governance on the Company's Capital Structure. The variable used in this study were director size, outside commissioner, director ownership, institutional investor, audit quality, CEO tenure, size, growth, profitability, and intangible asset. This research used a quantitative approach with multiple linear regression analysis model. This research used samples taken from non-financial sector companies listed on the Indonesia Stock Exchange (BEI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 8 publications
4
18
2
Order By: Relevance
“…Mwambuli ( 2019 ) investigates the role of CG, measured by a CGI, on CS of 32 non-financial listed firms in the East African region from 2006 to 2015 and finds a significant negative effect of CG on CS decisions. Most studies (Herlambang et al 2018 ; Chow et al 2018 ) use several CG variables as a proxy for CG, and the use of CGI as a measure of overall CG quality to assess their impact on CS is rare.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mwambuli ( 2019 ) investigates the role of CG, measured by a CGI, on CS of 32 non-financial listed firms in the East African region from 2006 to 2015 and finds a significant negative effect of CG on CS decisions. Most studies (Herlambang et al 2018 ; Chow et al 2018 ) use several CG variables as a proxy for CG, and the use of CGI as a measure of overall CG quality to assess their impact on CS is rare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies related to CS in Mauritius have focused on the determinants of CS (Fowdar et al 2009 ; Odit and Gobardhun 2011 ; Gourdeale and Polodoo 2016 ; Omrawoo et al 2017 ), and so far, only one study has been conducted on the effect of CS on FP by Seetanah et al ( 2014 ), with limited sample size and no CG variables employed as potential determinants. Fifth, no study has been conducted on the impact of CG on CS and vice versa in Mauritius, and most studies (Herlambang et al 2018 ; Chow et al 2018 ) have used several CG variables as proxies for CG. The use of CGI as a measure of overall CG quality to assess its impact on CS is rare.…”
Section: Introductionmentioning
confidence: 99%
“…What corporate governance factors affect the company's capital structure has yet to be discovered. Several prior studies that looked at the relationship between corporate governance and capital structure, including those by Detthamrong et al (2017), Herlambang et al (2018), Siromi and Chandrapala (2017), and Sheikh (2019), have produced conflicting findings. As a result, more research into this topic is encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…Detthamrong et al (2017) found that the board size variable had a positive but insignificant effect on leverage. Meanwhile, research conducted by Herlambang et al (2018) shows that the size of the commissioners' board significantly negatively affects leverage. On the other hand, Siromi and Chandrapala (2017) and Kumalasari et al (2019) found that board size has a negative but insignificant effect on leverage.…”
Section: Introductionmentioning
confidence: 99%
“…The Dividend Payout Ratio policy within the company has an important impact on the many parties involved in it. Dividend policy is a policy that is carried out at a cost that is quite expensive, because companies must provide large amounts of funds for dividend payments (Farrukh, et.al., 2017;Herlambang, Murhadi, & Susanto, 2018). For shareholders or investors, dividends are the rate of return on their investment in the form of share ownership issued by other companies.…”
Section: Introduction *mentioning
confidence: 99%